Pembatalan Pengalihan Hak Atas Merek Terdaftar Pada Dirjen Merek (Studi Kasus Merek “Bikers Brotherhood Mc”) - Ahmad Fauzi (Universitas Muhammadiyah Yogyakarta, 2023)
The transfer of rights to a trademark is one of the mechanisms for transferring rights to a brand to another party. Transfer of trademark rights can be done in various ways, one of which is by agreement. The agreement on the transfer of rights to the trademarks of both parties has occurred, then the transfer of rights to the marks will be registered with the Director General of Intellectual Property Rights. In cases where the Director General of Intellectual Property Rights does not have the authority to cancel the transfer of trademark rights, the Trademark Law does not regulate the procedure for canceling trademark rights that have been registered. So that it is necessary to renew the law by revising the Trademark Law regarding the mechanism for canceling the transfer of rights to a Mark. This research was conducted by means of literature study.